Computational Anatomy Based on Whole Body Imaging Basic Principles of Computer-Assisted Diagnosis and Therapy - Kobatake, Hidefumi; Masutani, Yoshitaka; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book deals with computational anatomy, an emerging discipline recognized in medical science as a derivative of conventional anatomy. It is also a completely new research area on the boundaries of several sciences and technologies, such as medical imaging, computer vision, and applied mathematics. Computational Anatomy Based on Whole Body Imaging highlights the underlying principles, basic theories, and fundamental techniques in computational anatomy, which are derived from conventional anatomy, medical imaging, computer vision, and applied mathematics, in addition to various examples of applications in clinical data. The book will cover topics on the basics and applications of the new discipline. Drawing from areas in multidisciplinary fields, it provides comprehensive, integrated coverage of innovative approaches to computational anatomy. As well,Computational Anatomy Based on Whole Body Imaging serves as a valuable resource for researchers including graduate students in the field and a connection with the innovative approaches that are discussed. Each chapter has been supplemented with concrete examples of images and illustrations to facilitate understanding even for readers unfamiliar with computational anatomy.
Introduction -- Fundamental Theories and Techniques -- Understanding Medical Images Based on Computational Anatomy Models -- Applied Technologies and Systems -- Perspectives.
Keywords: Biomedical engineering; Radiology; Medical physics; Anatomy; Image processing -- Digital techniques; Computer vision; Dynamics; Nonlinear theories; Biomedical Engineering and Bioengineering; Radiology; Medical Physics; Anatomy; Computer Imaging, Vision, Pattern Recognition and Graphics; Applied Dynamical Systems